Establishment of a family court: Towards sustainability of family institution in Malaysian context - Che Soh @ Yusoff, Roslina (2011)
The diversity of the Malaysian populations resulted in the enactments of various laws governing their daily matters. In the administration of family laws, the Muslims and the non Muslims population are governed by separate legal systems that establish separate courts having exclusive jurisdictions on each population. In both jurisdictions, there is no single court which provides a comprehensive solution for family conflicts. The adjudication of family cases by different courts at present would only bring more hardship and pain to the families as it involves prolonged proceedings, high costs in terms of legal fees, time consuming and lack of appreciation and understanding on the part of different officials and legal personnel. The matter exacerbates especially in family disputes involving spouses having different religion because it involves jurisdictional conflict between the Shariah and the Civil Courts. The establishment of a family court system for both Muslims and non Muslims, with complete jurisdiction in all children's and family matters and manned by specialized judges who have the assistance of helping professionals, such as psychiatrists, psychologists, and marriage counselors seems to be the best alternative for family disputes resolution. The procedure would be less stressful and traumatic for the parties concerned and this in turn may encourage parties to resolve their differences amicably. Hence, it may significantly reduce litigation on family related disputes and promotes towards sustainability of family institution as a whole. This paper seeks to discuss the concept and philosophy of family court system and the justification of its establishments in Malaysia. The paper will also briefly discuss the implementation of family court system in Australia and Singapore as these countries have established a well developed family court system. The purpose is to learn their experiences in providing a comprehensive solution in resolving family related disputes.